Implementation of IoT-based practicum learning media for vocational students in the 4.0 era - Handy Ferdiansyah; Zulkifli N; Nurmayanti L Nurmayanti; Wahyudi Sofyan; Vina Tri Agustina; Muh Alief Efendy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This study aims to determine the implementation of the use of Internet of Things (IoT)-Based Automation Control Systems as a practical learning medium for students of SMK Negeri 3 Sidrap Competence in the Field of Plant Agribusiness and Horticulture. The sample of this study was class X students of Agribusiness Food Crops and Horticulture SMK Negeri 3 Sidrap, drawn using total sampling technique. Data collection techniques are direct observation of the activity process and observations made by teachers during practicum activities. The data analysis technique used is quantitative descriptive analysis by looking at the percentage of success of practicum implementation. Based on the results of the study, it can be seen that the implementation of the practice of soil temperature and moisture measurement subjects can be carried out well, as the results of observations on the implementation of activities reach a percentage of 100% and the results of observations using Internet of Things (IoT)-based Automation Control System media in practical learning by 100%. Thus, it can be concluded that the implementation of practicum can be done by implementing Internet of Things (IoT)-based Automation Control System media.